ANALISIS KEBERDAYAAN EKONOMI MASYARAKAT MISKIN MELALUI PROGRAM KELUARGA HARAPAN (PKH) DESA TINAMBUNGKECAMATAN PAMBOANGKABUPATEN MAJENE (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2023)
The main problem in this research is how to empower the community through the Family Hope Program in Tinambung Village, Pamboang District, Majene Regency. From this main problem, the researcher describes the problem in two sub-chapters, namely: 1) How is the implementation of the poor community empowerment program through PKH in Tinambung Village, Pamboang District, Majene Regency? 2) How is the development of the people of Tinambung Village, Pamboang District, after receiving assistance from the Family Hope Program? This study uses a qualitative approach the method used in this study is the narrative method and data collection is done using observation, interviews, and documentation. The data sources in this study are divided into two types: primary data sources consisting of five people, while secondary data sources come from relevant documents. The researcher also used a purposive sampling technique where the researcher selected informants according to the criteria and had a close relationship with the researcher. The analysis technique has three stages: data reduction, data presentation, and concluding. The results of the study show that: 1) The process of implementing the poor community empowerment program through PKH in Tinambung Village includes the regional and participant selection stages, the initial meeting and validation of prospective participants, the verification of eligibility, the data updating stage, and the initial fund disbursement stage, then 2) The development of the Tinambung Village community after receiving the Family Hope Program assistance, namely changes in economic conditions, changes in the quality of education, and changes in the quality of health.